Morfologické nálezy ve stĕnĕ trachey po dlouhodobé intubaci a tracheostomii - Chlumská, A; Michal, M; Marek, J (Ceskoslovenska patologie, 1997)
Investigation of tracheal wall in 27 patients showed flat ulcerations of mucosa majority of which was combined with marginal squamous metaplasia of superficial conspicuously proliferating epithelial layer. Squamous metaplasia of mucosal glands (sialometaplasia) was found around ulcerations in 14 cases. Fibroproductive inflammatory lesion of tracheal wall was accompanied by a serious destruction of cartilages reminding of that in relapsing chondritis. Regeneration of cartilages was found in 23 cases.
Keywords: senioři; Intubation, Intratracheal; trachea; senioři nad 80 let; tracheostomie; Middle Aged; mužské pohlaví; Tracheostomy; sliznice; Adult; intratracheální intubace; Aged, 80 and over; ženské pohlaví; Mucous Membrane; Humans; lidé středního věku; dospělí; Trachea; Female; Aged; lidé; Male